2022
DOI: 10.3389/fcvm.2022.1001883
|View full text |Cite
|
Sign up to set email alerts
|

Long-term single-lead electrocardiogram monitoring to detect new-onset postoperative atrial fibrillation in patients after cardiac surgery

Abstract: BackgroundPostoperative atrial fibrillation (POAF) is often associated with serious complications. In this study, we collected long-term single-lead electrocardiograms (ECGs) of patients with preoperative sinus rhythm to build statistical models and machine learning models to predict POAF.MethodsAll patients with preoperative sinus rhythm who underwent cardiac surgery were enrolled and we collected long-term ECG data 24 h before surgery and 7 days after surgery by single-lead ECG. The patients were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The analysis of ECG variables in the current study focused only on those parameters that are easily assessed in clinical practice; thus, some important but less frequently used variables might have been omitted. The proposed model showed high sensitivity for HCM screening, at the cost of a high false-positive rate He et al [ 43 ] The results of this study showed that long-term ECG monitoring could significantly improve the detection rate of postoperative atrial fibrillation. The model combining P wave parameters and clinical data performed better in predicting postoperative atrial fibrillation.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The analysis of ECG variables in the current study focused only on those parameters that are easily assessed in clinical practice; thus, some important but less frequently used variables might have been omitted. The proposed model showed high sensitivity for HCM screening, at the cost of a high false-positive rate He et al [ 43 ] The results of this study showed that long-term ECG monitoring could significantly improve the detection rate of postoperative atrial fibrillation. The model combining P wave parameters and clinical data performed better in predicting postoperative atrial fibrillation.…”
Section: Discussionmentioning
confidence: 85%
“…He et al [ 43 ] collected long-term ECG data 24 h before surgery and 7 days after surgery by single-lead ECG from 100 patients with preoperative sinus rhythm who underwent cardiac surgery. The patients were divided into a Postoperative atrial fibrillation (POAF) group and a no-POAF group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ML models used ECG input signal for AF detection (Agliari et al, 2020; Alhusseini et al, 2020; Buscema et al, 2020; Domazetoski et al, 2022; K. He et al, 2022; Huang et al, 2021; Nickelsen et al, 2017; Pérez‐Valero et al, 2019; Rad et al, 2021; Rouhi et al, 2021; Schaefer et al, 2014; Wesselius et al, 2022; Yao et al, 2021). Abdul‐Kadir et al (2016) developed an AF recognition method based on dynamic ECG features extracted using the concept of a second‐order dynamic system.…”
Section: Resultsmentioning
confidence: 99%
“…Most ML models used ECG input signal for AF detection (Agliari et al, 2020;Alhusseini et al, 2020;Buscema et al, 2020;Domazetoski et al, 2022;K. He et al, 2022;Huang et al, 2021;Nickelsen et al, 2017;Pérez-Valero et al, 2019;Rad et al, 2021;Rouhi et al, 2021;Schaefer et al, 2014;Wesselius et al, 2022;Yao et al, 2021).…”
Section: Atrial Fibrillation Detection With Machine Learningmentioning
confidence: 99%